Ischemic VSD - Ahmed, Mohamed S.; Ibrahim, Firas F. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Ischemic VSD or ventricular septal rupture (VSR) is a rare but lethal complication of myocardial infarction (MI). Multi-system coronary disease is present in more than 50% of these patients. The event occurs 2-8 days after an infarction and often precipitates cardiogenic shock. The differential diagnosis of postinfarction cardiogenic shock should exclude free ventricular wall rupture and rupture of the papillary muscles. To avoid the high morbidity and mortality associated with the disorder, patients should undergo emergent surgery. Concomitant coronary artery bypass may be required. Objective: This study stressed on a very serious complication of a common pathology (myocardial infarction), despite it,s lethal complication but still it is treatable and still surgery is the only salvageable option. Patients & methods: Retrospective study of 7 consecutive cases with ischemic VSR encountered from (1st Jan. 2008-30 of September 2011). All of the cases were carefully assessed & fully investigated preoperatively (by echocardiography study, catheterization ...etc) & for all of them emergency open heart surgery was done with heart lung machine to close a post infract VSD using synthetic patch and ventriculotomy closed with reinforced Teflon felts , all of them(except the last case which died immediately post operatively) stayed for 2-3 days in the CICU under follow up . Results: Seven patients have been operated upon, 4 males (57%) and 3 female (43%), and their ages ranged between 50-63 years (75% in the 6th decade). Three of them (43%) were diabetic only but all of them were hypertensive. All of them were haemodynamically unstable so operation carried on emergently within 12-18 days post infarction (one operation done within 27 hours of infarction) and in none of them the clinical status helped to postpone them until more than 3 weeks post infarct. Five Out of the seven patients survived the operation, one died immediately post operatively &another one died 7 days post operatively due to renal failure (due to pre operative impaired renal function). Operative & early post operative mortality is (28%). Conclusion: We need to be more aware about this fatal complication of acute MI taking in consideration its late presentation (2-8) days. We have to work hardly to improve early revascularization to decrease the incidence of VSR. Improvement in surgical technique using double patch and glue improve mortality & morbidity rates. More cases need to have a better understanding & management of these cases.